Isolation and characterization of a cDNA clone encoding the 19 kDa protein of signal recognition particle (SRP): expression and binding to 7SL RNA. - Lingelbach, K (1988)
Signal recognition particle (SRP) consists of a 7SL RNA molecule and 6 protein subunits. We have isolated and characterized cDNA clones from human liver which encode the 19kDa protein subunit (SRP19). This subunit binds to the RNA directly and mediates binding of a second polypeptide, the 54kDa subunit which is involved in signal sequence recognition. Amino acid sequences deduced from the human cDNA sequence were identical to amino acid sequences of tryptic peptides from canine pancreatic SRP19. In vitro transcription and translation of the human cDNA resulted in a protein product the same size as canine SRP19 which could be immunoprecipitated by an antiserum raised against canine SRP19. SRP19 synthesized in a cell-free system specifically bound to 7SL RNA. The sequence of SRP19 is discussed with respect to its binding to 7SL RNA.